Variable Temporal Cerebral Blood Flow Response to Acetazolamide in Moyamoya Patients Measured Using Arterial Spin Labeling - Fahlström, Markus; Wikström, Johan; Borota, Ljubisa; Enblad, Per; Lewén, Anders (Frontiers in Neurology, 2021)
Cerebrovascular reserve capacity (CVR), an important predictor of ischaemic events and a prognostic factor for patients with moyamoya disease (MMD), can be assessed by measuring cerebral blood flow (CBF) before and after administration of acetazolamide (ACZ). Often, a single CBF measurement is performed between 5 and 20 min after ACZ injection. Assessment of the temporal response of the vasodilation secondary to ACZ administration using several repeated CBF measurements has not been studied extensively. Furthermore, the high standard deviations of the group-averaged CVRs reported in the current literature indicate a patient-specific dispersion of CVR values over a wide range. This study aimed to assess the temporal response of the CBF and derived CVR during ACZ challenge using arterial spin labeling in patients with MMD. Eleven patients with MMD were included before or after revascularisation surgery. CBF maps were acquired using pseudo-continuous arterial spin labeling before and 5, 15, and 25 min after an intravenous ACZ injection. A vascular territory template was spatially normalized to patient-specific space, including the bilateral anterior, middle, and posterior cerebral arteries. CBF increased significantly post-ACZ injection in all vascular territories and at all time points. Group-averaged CBF and CVR values remained constant throughout the ACZ challenge in most patients. The maximum increase in CBF occurred most frequently at 5 min post-ACZ injection. However, peaks at 15 or 25 min were also present in some patients. In 68% of the affected vascular territories, the maximum increase in CBF did not occur at 15 min. In individual cases, the difference in CVR between different time points was between 1 and 30% points (mean difference 8% points). In conclusion, there is a substantial variation in CVR between different time points after the ACZ challenge in patients with MMD. Thus, there is a risk that the use of a single post-ACZ measurement time point overestimates disease progression, which could have wide implications for decision-making regarding revascularisation surgery and the interpretation of the outcome thereof. Further studies with larger sample sizes using multiple CBF measurements post-ACZ injection in patients with MMD are encouraged.